Політичні цінності і рекодифікація українського цивільного законодавства - Харитонов, Євген Олегович; Харитонов, Є. О.; Kharytonov, Yevhen; Харитонова, Олена Іванівна; Харитонова, О. І.; Kharytonova, Olena (ВД "Гельветика", 2020)
У статті аналізується значення політичних цінностей для формування традиції приватного права взагалі та в Україні зокрема. У процесі дослідження звертається увага на те, що концепт приватного права є властивим демократичному суспільству і не може повноцінно розвиватися в умовах суспільства авторитарного або такого, що тяжіє до авторитарного. Наголошується на необхідності врахування під час рекодифікації (оновлення) цивільного законодавства значення політичних цінностей, а також усунення колізії приватних та публічних цінностей, без чого рекодифікація цивільного законодавства не може бути успішною.

The article analyzes the importance of political values for forming the tradition of private law in general and in Ukraine in particular. In the course of the study, attention is drawn to the fact that the concept of private law is inherent in a democratic society and cannot be fully developed in an authoritarian or similar to it society. Features of Ukrainian political values are determined by Ukraine’s belonging to the frontier civilization. On the one hand, the recognition of such values as freedom, human rights, the Constitution, legality, civil society, etc., allegedly, does not cause doubt for Ukrainian jurists. At the same time, polls show that about two-thirds of Ukrainians are ready to hand over to the president-elect both the legislature and the executive power. Sociologists warn of the danger of chaos and disorganization, because most Ukrainians associate success not with the activities of state institutions, the efficiency of business or society, but only with a new person who has come to power. The immaturity of the political values of Ukrainians is also reflected in the fact that there is still no real political system in Ukraine. Therefore, in the elections, everyone goes left and then pursues the right policy. Experts explain this by saying that social-democratic politics is only possible in relatively prosperous societies, and in the poor, like Ukraine, for the country to get rich, politics must be right. This policy opens the way for businesses, allows them to redistribute less and invest more in business development. But the needy class wants taxes to be higher and business to be lower. Both supported the Party “Sluga narodu”, but it would not be able to pursue politics while reducing taxes and raising benefits at the same time. The belief of a large part of Ukrainians in the possibility of unfulfilled policy, their willingness to yield for the sake of the Constitution and legality, gives grounds for questioning such values as democratic elections, social initiative and so on. Given these circumstances, the article emphasizes the need to take into account while recoding (updating) of civil law values the meaning of political values, as well as the elimination of conflicts of private and public values, without which the recoding of civil law cannot be successful.
Харитонов Є. О. Політичні цінності і рекодифікація українського цивільного законодавства / Є. О. Харитонов, О. І. Харитонова // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 18-24.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; політичні цінності; демократія; авторитаризм; приватне право; цивільне законодавство; рекодифікація; political values; democracy; authoritarianism; private law; civil law; recodification